Procedures for auditing accounting violations according to international auditing : standards in the Karbala Municipality Directorate (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to identify the definitional framework for accounting violations and audit procedures in accordance with international auditing standards, preparing a proposed audit program to audit violations resulting from the transition to the unified accounting system in the research sample according to the relevant international auditing standards, as the proposed audit program was prepared according to International auditing standards in order to improve the auditor’s procedures in detecting accounting violations when auditing the financial statements of municipal departments. The research concluded the most important recommendations: The necessity of adopting the audit program proposed by the researcher, for the purpose of activating audit procedures in detecting accounting violations in the financial statements and obligating them to do so